MORPHOLOGICAL COMPARISON OF THREE ASIAN NATIVE HONEY BEES (APIS CERANA, A. DORSATA, A. FLOREA) IN NORTHERN VIETNAM AND THAILAND - N.V. NIEM; L. Q. TRUNG (SEAMEO BIOTROP, 1999)
Three species of Asian native honey bees (Apis cerana, A. florea and A. dorsata) from northern Vietnam and Thailand were morphologically analyzed for investigations on their geographic variations and relations. In Vietnam, samples were collected from feral and managed colonies. In Thailand, the collections were from feral colonies or from field bees on flowers. Morphological analysis was carried out, using measurements common to honeybee taxonomy. Measured characters were done under stereomicroscope with an ocular micrometer. ANOVA program and multivariate statistical analyses were applied for treating the data. Overall, A. cerana populations in northern Vietnam are significantly morphologically different than from those in Thailand. It may be due to their different geographic locations between the Thai and Vietnamese populations of A. cerana. A. florea bees from Vietnam are generally bigger in size than those from Thailand, but the differences are uncertain. In contrast, the body size of A. dorsata populations from Thailand are bigger than those from Vietnam. However, these differences are also not significant. It is necessary to take further comparative investigations of these bee species from both countries. Key words: Honey bee/Apis cerana/Apis dorsata/ApisJlorea/moif>ho